Analisis Struktur Mikro Globular Dan Kekerasan Paduan Aluminium ADC12 Pada Pengecoran Semi Solid Dengan Metode Stir Casting - Syaharuddin Rasyid; Abram Tangkemanda; Muh. Hasmar Hasbullah; Muh. Andra Al-Fandi (Jurnal Teknik Mesin Sinergi, 2019)
This study aims to analyze the effect of the stirrer model, stirring rotation (400, 500, 600 rpm), for 20 seconds, and pouring temperature (565, 570, and 5750C) on the microstructure and mechanical properties of the aluminum alloy ADC12. The methods of research are a) preparing material aluminum alloy ADC12, b) making molds, c) casting, d) making specimens for testing, e) micro structure testing and hardness testing, f) analyzing data using Microsoft excel applications. Results of the study show that the smallest grain size occurs in casting parameters: stirrer angle 00, 600 rpm rotation, and pouring temperature 5650C with a value of 27.715 µm. The biggest shape factor occurs in casting parameters: stirrer angle 00, rotation 600 rpm, and pouring temperature 5650C with a value 0.76. The highest hardness occurs in casting parameters: stirrer angle 00, rotation 600 rpm, and pouring temperature 5650C with a value 88.0 HB.